(untitled) (Eurasian Research Bulletin, 2023)
It is impossible to imagine without maintaining the sustainable development of the oil and gas sector, which serves as a raw material base for the development of the petrochemical industry not only in the conditions of high growth rates of the republic, but also the country’s energy resources. at least 7-8% per annum. From this point of view, one of the most important problems in the development of the oil and gas sector is its inefficient management system. The analysis showed that JSC "Uzbekneftegaz" is actively developing, at the same time, it was revealed that enterprises in the oil and gas sector need additional investment resources and poorly use such main sources of borrowing and investment resources as the stock market.